the writing of sterility in Yodi Karone’s : negre de paille - Bakenga, Emile Baderha; Bashombana, Ezéchiel Kanyama (IJRDO- Journal of Educational Research, 2021)
Literature helps the reader understand well the word he lives in, discover himself and juge himself according to norms and sociocultural and economic realities of his time and society in yodi karone’s « negre de paille », makes a reading of the writing of sterility in the corpus . The author uses figurative constructions of sterility relying on some figures of speech, such as monologue, analepsis and prolepsis as being key procedures that the author use to produce this writing of sterility ; The failure focused on in this study is yoyo dibanga’s lack of procreation, a taxi driver married to a woman teacher named carlota dibanga’s. . The misfortune is that the couple could not have a child and the problem bothered the women so hard. She rounds out that her husband stays indifferent which irritates her as she has to struggle alone. Unfortunately, during an ordinary picnic, yoyo discovers that his wife is unfaithful. That act unsettled him much as his cousin was his rival. Despite his efforts to endure such an insult, he failed and ends to make an accident that led to his loss ; the author uses some mechanisms of literary creation to write and epress his throughts on peopole’s everyday life ; however, the sterility referred to in the novel surpasses the sterility as lack of procreation. it would on top of that designate the failure of governance in some african strates ; where coups, genocides, rapes ; endless wars reign which lead to african chaos and disillusionment of literature ;